2021
DOI: 10.1177/01623532211001440
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Interactive Cognitions of Differentiated Instruction: An Exploration in Regular and Talent Development Lessons

Abstract: Differentiated instruction (DI) is an effective instructional strategy to maximize individual students’ abilities; in practice, however, its implementation appears to be problematic. To better understand teachers’ perspectives on DI and the effect different teaching contexts can have, we explored teachers’ interactive cognitions of DI in their regular lessons and in “talent lessons.” Four stimulated recall interviews were conducted with a sample of secondary school teachers ( n = 4) in the Netherlands. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Therefore, Differentiated Instruction can help teachers create more personalized and relevant learning experiences for students, which in turn can improve learning motivation and academic achievement (Brigandi et al, 2019). In the context of trends in the field of education, Differentiated Instruction demonstrates the importance of accommodating individual differences among students in teaching and learning (Stollman et al, 2021). It also shows that teachers must consider various learning methods and strategies to meet the diverse needs of students, including the use of technology to support learning.…”
Section: Trending and Relevant Topics For Future Researchmentioning
confidence: 99%
“…Therefore, Differentiated Instruction can help teachers create more personalized and relevant learning experiences for students, which in turn can improve learning motivation and academic achievement (Brigandi et al, 2019). In the context of trends in the field of education, Differentiated Instruction demonstrates the importance of accommodating individual differences among students in teaching and learning (Stollman et al, 2021). It also shows that teachers must consider various learning methods and strategies to meet the diverse needs of students, including the use of technology to support learning.…”
Section: Trending and Relevant Topics For Future Researchmentioning
confidence: 99%
“…This method was particularly important for this research, as while it can be observed by a researcher that teachers choose to engage in differentiation or not in their classroom, the researcher is unable to observe perceptions of teachers. According to Stollman et al (2021), most of the studies surrounding DI utilise observations and semi-structured interviews related to teacher knowledge and practices of DI; however, they believe that more focus needs to be on methods understanding teachers' unconscious cognitions during teacher practices. Therefore, this notion influenced the decision to include evidence artefacts, such as lesson plans, to complement the conscious interactions that teachers have during semi-structured interviews.…”
Section: Methodsmentioning
confidence: 99%
“…According to Stollman et al. (2021), most of the studies surrounding DI utilise observations and semi‐structured interviews related to teacher knowledge and practices of DI; however, they believe that more focus needs to be on methods understanding teachers’ unconscious cognitions during teacher practices. Therefore, this notion influenced the decision to include evidence artefacts, such as lesson plans, to complement the conscious interactions that teachers have during semi‐structured interviews.…”
Section: Methodsmentioning
confidence: 99%
“…Teknik analisis data dilakukan dengan mengumpulkan data responden yang dibutukan, menyeleksi data, melakukan pengkodean, dan penyajian data. Kuesioner pada penelitian ini berbasis pada indikator interaksi guru dan siswa yang dikembangkan oleh (Stollman et al, 2021): Tabel 1. Indikator Interaksi Guru dan Siswa Tipe Interaksi Deskripsi Penetapan tujuan pembelajaran Guru secara eksplisit menetapkan tujuan dan/atau mencoba menetapkan konteks awal dengan menjelaskan dikelas secara eksplisit atau implisit dengan mempertimbangkan kemampuan awal siswa.…”
Section: Metodeunclassified